Employee-experienced High-performance Work Systems in Facilitating Employee Helping and Voice: The Role of Employees' Proximal Perceptions and Trust in the Supervisor. Issue 2 (15th March 2019) - Wang, Chun-Hsiao; Baba, Vishwanath V.; Hackett, Rick D.; Hong, Ying
ABSTRACT: Relative to previous research concerning the positive association between high-performance work systems (HPWS) and employees' voice and helping, we examined a wider range of mediators reflecting employees' ability, motivation, and opportunity to expand their citizenship-based role definitions. Trust in the supervisor was also investigated as a boundary condition on the relationships in question. Multisource data, collected in 4 waves, from 208 supervisor–employee dyads showed that employees' efficacy, instrumentality, and autonomy perceptions concerning voice mediated the association between employee-experienced HPWS and expanded role definition for voice. Instrumentality mediated the relationship between employee-experienced HPWS and expanded role definition for helping. The positive links between employee-experienced HPWS and both supervisor-rated helping and voice were mediated by employees' role definitions. Trust in the supervisor positively moderated the mediated effects.